2022
DOI: 10.5232/ricyde2022.06801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tournament format change on team performance of Chinese Football Super League during COVID-19 pandemic. [Efecto del cambio de formato del torneo en el rendimiento del equipo de la Superliga de China de Fútbol durante la pandemia de COVID-19].

Abstract: The outbreak of COVID-19 forced Chinese Football Association to adopt a special format for the 2020 Chinese Football Super League (CSL) after 5-month suspension. All 160 matches (decreased from 240) were divided into two stages (round robin; two-legged knockout) and played behind closed doors in two neutral cities (Suzhou and Dalian). The purpose of this study was to investigate the influence of absence of spectators and format change on teams’ winning percentage and match performance. Technical-tactical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Among the theoretical works, three studies were unclassified since they did not include original data analysis (Gouveia & Pereira, 2021;Richlan et al, 2023;Webb, 2021). Overall, there were only 7 total studies (14.9%) that could not be classified by research phase and home advantage effect (Gouveia & Pereira, 2021;Jiang et al, 2021;Magistro & Wack, 2023;Richlan et al, 2023;Steinfeldt et al, 2022;Webb, 2021;Wilkesmann, 2022), highlighting that the vast majority of works clearly assessed impacts on home advantage. By integrating research phase and quantifying observed effects, Table 3 provides greater specificity regarding trends in findings than considering these dimensions individually.…”
Section: Variation Of Home Advantage After Covid-19mentioning
confidence: 99%
“…Among the theoretical works, three studies were unclassified since they did not include original data analysis (Gouveia & Pereira, 2021;Richlan et al, 2023;Webb, 2021). Overall, there were only 7 total studies (14.9%) that could not be classified by research phase and home advantage effect (Gouveia & Pereira, 2021;Jiang et al, 2021;Magistro & Wack, 2023;Richlan et al, 2023;Steinfeldt et al, 2022;Webb, 2021;Wilkesmann, 2022), highlighting that the vast majority of works clearly assessed impacts on home advantage. By integrating research phase and quantifying observed effects, Table 3 provides greater specificity regarding trends in findings than considering these dimensions individually.…”
Section: Variation Of Home Advantage After Covid-19mentioning
confidence: 99%